(untitled) - Banyavongsa, Anna (Cần Thơ, 2019)
The main objective of this study was to develop purple rice milk from purple rice with higher nutritional and good quality. Purple rice (ST) which was cultivated in Soc Trang province, Viet Nam was used for this research because this variety of rice has high amount of nutrients and a lot of benefits for health.
Keywords: Rice milk,Sữa gạo